1993
DOI: 10.1161/01.atv.13.11.1623
|View full text |Cite
|
Sign up to set email alerts
|

LDL size and subclass pattern in a biethnic population.

Abstract: Recently, the presence of small, dense low-density lipoprotein (LDL) has been recognized as a risk factor for coronary heart disease. There has been little work on correlates of LDL size in population-based studies and none in Mexican Americans. We examined the relationship of LDL size and pattern to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 41 publications
5
22
0
4
Order By: Relevance
“…However, triglycerides returned to baseline values at study week 24. In other populations, serum triglycerides are inversely related to LDL particle size (18,27). In our subjects, decreases in triglycerides were associated with a favorable increase in LDL particle size (r ϭ Ϫ0.59, P ϭ 0.001).…”
Section: Discussionsupporting
confidence: 52%
“…However, triglycerides returned to baseline values at study week 24. In other populations, serum triglycerides are inversely related to LDL particle size (18,27). In our subjects, decreases in triglycerides were associated with a favorable increase in LDL particle size (r ϭ Ϫ0.59, P ϭ 0.001).…”
Section: Discussionsupporting
confidence: 52%
“…Triglyceride concentrations predict by 60% the size of LDL [8]. Other parameters related to LDL size were tested in our work.…”
mentioning
confidence: 99%
“…The fasting plasma insulin concentration correlates positively with whole plasma and VLDL triglycerides and negatively with HDL cholesterol even in multivariate analyses controlled for important confounders such as age, sex, glucose tolerance, obesity and body fat distribution. Population-based studies have also reported associations between fasting plasma insulin and lipoprotein subclasses such as the inverse relations to the LDL peak particle size [4] and the HDL 2 cholesterol concentration [5]. Furthermore, the plasma insulin concentration has proved to be related to the production of large VLDL particles with a Svedberg flotation (Sf) rate of 60 to 400 in experimental studies in humans using a stable isotope technique [6].…”
mentioning
confidence: 99%